Determinan Pertumbuhan Ekonomi Dalam Model Perekonomian Tiga Sektor - Ranti Darwin (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2020)
This study aims to analyze the determinants of economic growth on the three sector economic model. The research method used is a quantitative method with panel data regression analysis using STATA 15.0 software. This study uses secondary time series data for the period 2006-2018. The results of this study explain that consumption has an influence on economic growth between regions in Riau Province. In addition, investment and government expenditure variables do not have an influence on economic growth between regions in Riau Province.